2013
DOI: 10.1111/ane.12130
|View full text |Cite
|
Sign up to set email alerts
|

Predicting health-related quality of life 2 years after moderate-to-severe traumatic brain injury

Abstract: Aims -To describe health-related quality of life (HRQL) 2 years after moderate-to-severe traumatic brain injury (TBI) and to assess predictors of HRQL. Materials and methods -A prospective cohort study of 91 patients, aged 16-55 years, admitted with moderate-tosevere TBI to a trauma referral centre between 2005 and 2007, with follow-up at 1 and 2 years. Mean age was 31.1 (SD = 11.3) years, and 77% were men. Injury severity was evaluated by the Glasgow Coma Scale (GCS), head CT scan (using a modified Marshall C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
71
4
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 36 publications
9
71
4
6
Order By: Relevance
“…Although controversies may exist concerning the disabilities associated with mild TBI (18), it is generally agreed that survivors of moderate-to-severe TBI are at increased risk of various degrees of permanent disability. Our cohort included patients with mild, moderate, and severe TBI and still showed QoL impairment, sleep disturbances, fatigue, depression, and sexual dysfunction at comparable rates to previous reports (19).…”
Section: Discussionsupporting
confidence: 59%
“…Although controversies may exist concerning the disabilities associated with mild TBI (18), it is generally agreed that survivors of moderate-to-severe TBI are at increased risk of various degrees of permanent disability. Our cohort included patients with mild, moderate, and severe TBI and still showed QoL impairment, sleep disturbances, fatigue, depression, and sexual dysfunction at comparable rates to previous reports (19).…”
Section: Discussionsupporting
confidence: 59%
“…However, the relationship between CT scan findings and QoL has been poorly studied, which explains the reason for this report. Some studies demonstrate this relationship [12,13], although these deal with patients in less serious situations than those admitted to the ICU or with smaller groups of patients or they do not consider and examine every single category of the Marshall classification or the relationship between CT and QoL in depth, as has been done in this study. This study analysed these aspects in a sample of ICU patients which was large enough to study QoL in most categories of the Marshall classification.…”
Section: Discussionmentioning
confidence: 94%
“…The association between lesions found on CT and mortality is widely known and has been documented in many studies [3,[8][9][10][11], as well as the association with other factors such as the initial Glasgow Coma Scale (GCS), APACHE II, ISS. The association between the Marshall CT classification and mortality and functional outcomes has been described extensively in the literature [3,[11][12][13], but the relationship between cranial CT findings and QoL has been poorly studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the GOSE, HRQL measures enable comparison of health outcome after TBI with other diseases and the general population, and their outcome in terms of an health status on a scale from 0 (death) to 1 (perfect health) scale can be used in economic evaluations. Research has shown that even years after injury, many TBI patients still report significantly lower HRQL than the general population [1,2,[11][12][13][14]. Most studies however, focus on recovery after mild [15][16][17] or moderate and severe [1,12,13,18,19] TBI.…”
mentioning
confidence: 99%